Foreign investment activities of Chinese companies - Antevski Miroslav; Filipović Sanja (Međunarodni Problemi)
Chinese investments abroad have recorded high growth rates in the last decade, but its scope is still small in comparison to those of developed industrial countries. The state plays a key role in its encouragement and support directly and indirectly. Large state corporations are the biggest investors abroad, somewhere investments of Chinese private companies dominate, e.g. in Africa. There is a great geographic dispersion of investment flows, while the highest concentration is in developing countries. The main drivers of investment capital are trade, energy sources, natural resources, infrastructure projects and acquisition of strategic assets. These drivers are often are combined from two or more ones which are mutually supportive. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima - spoljnopolitički, međunarodnoekonomski, pravni i bezbednosni aspekti, br. 179011: Organizacione i informacione podrške sistemu upravljanja kvalitetom kao ključnim faktorom povećanja konkurentnosti naših preduzeća i njihovog bržeg ulaska na svetsko i EU tržište i br. 47009: Evropske integracije i društveno-ekonomske promene privrede Srbije na putu ka EU]